Iterative learning fault-tolerant control for differential time-delay batch processes in finite frequency domains. (August 2017) - Tao, Hongfeng; Paszke, Wojciech; Rogers, Eric; Yang, Huizhong; Gałkowski, Krzysztof
Abstract : Highlights: Finite frequency range ILC law design is extended to fault tolerant control problem. Time-delay differential batch process with actuator fault is considered. Monotonic trial-to-trial error convergence conditions for ILC dynamics are derived. The extension to robust control against structured uncertainty is developed. Abstract: This paper develops a fault-tolerant iterative learning control law for a class of differential time-delay batch processes with actuator faults using the repetitive process setting. Once the dynamics are expressed in this setting, stability analysis and control law design makes use of the generalized Kalman–Yakubovich–Popov (KYP) lemma in the form of the corresponding linear matrix inequalities (LMIs). In particular, sufficient conditions for the existence of a fault-tolerant control law are developed together with design algorithms for the associated matrices. Under the action of this control law the ILC dynamics have a monotonicity property in terms of an error sequence formed from the difference between the supplied reference trajectory and the outputs produced. An extension to robust control against structured time-varying uncertainties is also developed. Finally, a simulation based case study on the model of a two-stage chemical reactor with delayed recycle is given to demonstrate the feasibility and effectiveness of the new designs.